Characterization of TMC-1 in C. elegans sodium chemotaxis and sodium conditioned aversion - Joseph Dao; Aileen Lee; Dana K. Drecksel; Nicole M. Bittlingmaier; Theodore M. Nelson (BMC Genetics, 2020)
Abstract Background While sodium is attractive at low and aversive at high concentrations in most studied species, including Caenorhabditis elegans, the molecular mechanisms behind transduction remain poorly understood. Additionally, past studies with C. elegans provide evidence that the nematode’s innate behavior can be altered by previous experiences. Here we investigated the molecular aspects of both innate and conditioned responses to salts. Transmembrane channel-like 1 (tmc-1) has been suggested to encode a sodium-sensitive channel required for sodium chemosensation in C. elegans, but its specific role remains unclear. Results We report that TMC-1 is necessary for sodium attraction, but not aversion in the nematode. We show that TMC-1 contributes to the nematode’s lithium induced attraction behavior, but not potassium or magnesium attraction thus clarifying the specificity of the response. In addition, we show that sodium conditioned aversion is dependent on TMC-1 and disrupts not only sodium induced attraction, but also lithium. Conclusions These findings represent the first time a role for TMC-1 has been described in sodium and lithium attraction in vivo, as well as in sodium conditioned aversion. Together this clarifies TMC-1’s importance in sodium hedonics and offer molecular insight into salt chemotaxis learning.